Applied sport management skills / Robert N. Lussier, PhD, David C. Kimball, PhD. - Lussier, Robert N.; Kimball, David Charles, 1959- (Human Kinetics, 2024)
This title uses the four management functions of planning, organising, leading and controlling to teach readers how to become strong leaders and managers in the world of sport.